2017
DOI: 10.1039/c6cc10330h
|View full text |Cite
|
Sign up to set email alerts
|

A GSH-activatable ruthenium(ii)-azo photosensitizer for two-photon photodynamic therapy

Abstract: A glutathione (GSH)-activatable ruthenium(ii)-azo photosensitizer was prepared. The complex had low toxicity towards cells under dark conditions. It exhibited excellent phototoxicity under two-photon excitation (810 nm) and thus was developed as a two-photon photodynamic anticancer agent for cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 45 publications
2
73
0
Order By: Relevance
“…Moreover, Chao’s group utilized a GSH-activatable Ru(II)-azo photosensitizer, ( 15b ), for two-photon PDT. 265 15b did not show luminescence but exhibited a strong luminescence after incubation in HeLa cells due to the activation of intracellular GSH. 15b accumulated to a significant extent in mitochondria and could produce ROS in HeLa cells upon two-photon irradiation (810 nm, 100 mW).…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, Chao’s group utilized a GSH-activatable Ru(II)-azo photosensitizer, ( 15b ), for two-photon PDT. 265 15b did not show luminescence but exhibited a strong luminescence after incubation in HeLa cells due to the activation of intracellular GSH. 15b accumulated to a significant extent in mitochondria and could produce ROS in HeLa cells upon two-photon irradiation (810 nm, 100 mW).…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 94%
“…In contrast, 15b was significantly cytotoxic in MCTSs, with an IC 50 value as low as 5.71 μM upon two-photon irradiation. 265 The Chao et al study demonstrated that the combination of organelle-targeting and two-photon activation provides a valuable paradigm for developing Ru(II) complexes for PDT applications.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 99%
“…[83] More recently, the group of Choi showedt hat an azo-based binuclear ruthenium(II) complex, Ru-azo, could also be used as as mart photosensitizer in two-photon photodynamic anticancer therapy( Figure17b). [84] Indeed, this complex showed high accumulation in the mitochondria of cancer cells and produced efficient photocytotoxicity upon bioreductive activation by GSH and two-photon excitation at l = 810 nm.…”
Section: Fluorescence Activation Throughreductive Cleavage Of the Azomentioning
confidence: 99%
“…As a highly relevant application, azo‐based iridium(III) complexes (IrX) have been used as multicolor phosphorescent probes to detect hypoxia in both adherent living cells and oxygen‐gradient 3D multicellular spheroids at depths of over 100 μm, which have many similarities to the in vivo environment (Figure d) . More recently, the group of Choi showed that an azo‐based binuclear ruthenium(II) complex, Ru–azo, could also be used as a smart photosensitizer in two‐photon photodynamic anticancer therapy (Figure b) . Indeed, this complex showed high accumulation in the mitochondria of cancer cells and produced efficient photocytotoxicity upon bioreductive activation by GSH and two‐photon excitation at λ =810 nm.…”
Section: Azo‐based Fluorogenic Probesmentioning
confidence: 99%
“…GSH is a necessary molecule for the adjusting of oxidation‐reduction state in living subjects . Recently, Fan and co‐workers developed a cyanine derivative‐based nanoprobe (IR806‐PDA) for in vivo PAD of GSH .…”
Section: Applications Of Photoacoustic Detectionmentioning
confidence: 99%